2015
DOI: 10.5125/jkaoms.2015.41.4.194
|View full text |Cite
|
Sign up to set email alerts
|

Repair of an oroantral communication by a human amniotic membrane: a novel technique

Abstract: The amniotic membrane is the innermost layer of fetal membrane and is attached to the chorion in the placenta. This membrane has been used for nearly a century in varied fields such as ophthalmology, reconstructive surgery, and burn treatment. In this case report, we used a human amniotic membrane to repair an iatrogenic oroantral communication that occurred during the extraction of the patient's right upper second molar. A splint was given after the perforation was covered with human amniotic membrane and hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…It has been widely recognized that AM can exert anti-inflammatory, antiangiogenic, antifibrotic, and antimicrobial effects 12 , 27 . A number of clinical studies have used the AM for applications in regenerative medicine 17 , 28 30 , but it has yet to be elucidated whether the different areas of the placenta have the same plasticity and differentiation potential. One study has recently demonstrated that placental amnion possesses a slightly higher metabolic activity and significantly lower ROS content, when compared to reflected amnion, which could suggest diverse cell differentiation capacities between the 2 regions 20 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been widely recognized that AM can exert anti-inflammatory, antiangiogenic, antifibrotic, and antimicrobial effects 12 , 27 . A number of clinical studies have used the AM for applications in regenerative medicine 17 , 28 30 , but it has yet to be elucidated whether the different areas of the placenta have the same plasticity and differentiation potential. One study has recently demonstrated that placental amnion possesses a slightly higher metabolic activity and significantly lower ROS content, when compared to reflected amnion, which could suggest diverse cell differentiation capacities between the 2 regions 20 .…”
Section: Discussionmentioning
confidence: 99%
“…More recently, decellularized AM has been employed for postinfarct left ventricular remodeling 16 and for the repair of an oroantral communication 17 , thus generating new questions as to the therapeutic potential of the different regions and/or cells in the AM. Indeed, only a handful of reports have characterized and studied the phenotype of the cells comprising the AM in situ 18 , 19 .…”
Section: Introductionmentioning
confidence: 99%
“…The amnion is the deepest layer of the human placenta [8][9][10][11][12][13][14][15][16][17][18][19] , and it has distinctive properties. It is made up of three lamina: an overlying tissue, a basement sheath, and a stromal layer beneath 13,14 . It possesses the unique property of low immunogenicity, which makes it an excellent grafting material.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the mentioned disadvantages of surgical procedures, various alternative techniques for OAC closure have developed recently. These contain use of alloplastic materials (bio‐absorbable root analogues, hydroxyapatite), auto‐transplantation (bone transplant, third molar transplant), allo‐transplantation (fascia lata, dura mater, Human amniotic membrane), xenografts (bone materials, Collagen), prosthetic management and guided tissue regeneration techniques including autologous platelet or leukocytes (platelet‐rich fibrin and platelet‐ and leukocyte‐rich fibrin) 1,10,16,11,19,20 . Figure 1 shows the currently used techniques for OAC closure.…”
Section: Introductionmentioning
confidence: 99%